The Role of Synbiotics in Modulating the Gut–Brain Axis in Attentiondeficit/Hyperactivity Disorder: A Systematic Review - Elfrida Noor Auliya; Margarita M. Maramis (CV. Publikasi Indonesia, 2026)
ADHD is a neurodevelopmental disorder involving gut microbiota dysbiosis and gut–brain pathways, suggesting synbiotics as a potential adjuvant therapy. Literature searches were conducted on electronic primary databases